Thrombotic thrombocytopenic purpura - Knöbl, Paul (Memo, 2018)
Thrombotic thrombocytopenic purpura (TTP) is a clearly defined entity of the thrombotic microangiopathies (TMA), a heterogeneous group of disorders characterized by microangiopathic hemolytic anemia with red cell fragmentation, thrombocytopenia and organ dysfunction due to disturbed microcirculation. TTP is characterized by a severe deficiency of ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13), an enzyme responsible for physiological cleavage of von Willebrand factor (VWF). Organ dysfunction can be severe and life-threatening, and immediate start of appropriate therapy is necessary to avoid permanent damage or death. Until recently, therapeutic options were limited to symptomatic measures, which were not standardized or based on high scientific evidence. In recent years, not only considerable progress has been made in better diagnosis of TTP, but also new therapeutic strategies have been established. Initial treatment is still based on plasma exchange and symptomatic measures to protect organ function, but new concepts (immunosuppression, targeted anti-VWF or anti-complement therapy, replacement with recombinant enzymes) have recently demonstrated impressive advantages.